A facile one-pot synthesis of CaO/CuO hollow microspheres featuring highly porous shells for enhanced CO2 capture in combined Ca-Cu looping process via a template-free synthesis approach - Chen, Jian; Duan, Lunbo; Shi, Tian; Bian, Ruoyu; Lu, Yuxiao; Donat, Felix; Anthony, Edward J. (Royal Society of Chemistry, 2019)
The preparation of bifunctional CaO/CuO composites with high performance is essential for the development of the combined Ca–Cu looping process, in which the exothermic reduction of CuO with methane is used in situ to provide the heat required to calcine CaCO3. However, the rapid decline in CO2 uptake of CaO/CuO composites remains an important problem to be solved, despite their excellent redox characteristic. Herein we report a facile one-pot template-free synthesis approach to yield CaO/CuO hollow microspheres, aimed at enhancing the CO2 capture performance of CaO/CuO composites. CaO/CuO hollow microspheres feature highly porous shells and a homogeneous elemental distribution, and demonstrate significantly enhanced CO2 capture performance. After ten repeated cycles in a fixed-bed reactor, the CO2 uptake capacity of the best-performing CaO/CuO hollow microspheres exceeded that of the reference materials, i.e., CaO/CuO composites synthesized via wet mixing or a co-precipitation method, by 222% and 114%, respectively. Moreover, from cycle number eight onwards, the CO2 uptake was very stable over the tested 20 cycles, suggesting good cyclic stability of CaO/CuO hollow microspheres. Oxidation was always fast with O2 uptake capacities greater than 0.13 gO2 gmaterial−1. On the basis of N2 adsorption, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) characterizations, the significantly enhanced CO2 capture performance of the CaO/CuO hollow microspheres resulted from the unique hollow microsphere structure with highly porous shells, which were retained throughout the cyclic operations.